STRATEGI MENYEIMBANGKAN PERAN KERJA DAN KELUARGA: STUDI FENOMENOLOGI PADA PEREMPUAN WIRAUSAHA - , Venisa Dwipa Sari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
High level of women participation in the economic sector and their developing involvement in business strengthen the interest to study women in terms of work-family life. Women nowadays play more roles, in the economic sector as business player and at home as the main caregiver for their children. This multiple-role creates more pressure on women thus inflicts friction and disharmony. Contradictory, this can also enable positive spillover, also inter-role enrichment and facilitation. This study aims to explore and understand how women involved in the business world balance their role demands and create work-family balance. Qualitative method with phenomenological perspective is used to gain data from subjects who are women entrepreneur with the criteria of: classified as âindependent womenâ, have one staff minimum, and married with children. The result of this study showed that the respondents balancing their role deman in bussiness and family by doing self-empowerment, and harmonization. Self-empowerment strategies involving personal management and becoming super women. Harmonization behavior involving religious behavior and interpersonal-familial management.